Analgesic Effect of Ethanol Extract Mangrove (Avicennia alba) and Soursop (Annona muricata) Leaves in Mice - Irianingsih, Iin; Nurcahyani, Nuning; Mumtazah, Dzul Fithria (LenteraBio : Berkala Ilmiah Biologi, 2025)
Analgesic drugs are drugs that can reduce pain due to tissue damage. Efforts are made to relieve pain by using non-steroidal anti-inflammatory drugs (NSAIDs). Long-term use of NSAIDs has side effects such as digestive tract disorders, kidney and liver damage, and skin allergies, so alternative herbal medicines are needed that have lower side effects, one of which is using mangrove Secondary metabolite compounds such as flavonoids and tannins from ethanol extract leaves of mangrove (Avicennia alba) and soursop (Annona muricata) function as analgesics that inhibit prostaglandin biosynthesis. This study uses the writhing test method to determine the analgesic activity of ethanol extract from mangrove (Avicennia alba) and soursop (Annona muricata) leaves in male mice. This research was experimental using a posttest-only control research design using 25 mice with 5 treatment groups, namely the negative control group Na-CMC 0.5%, the positive control group mefenamic acid, the Avicennia alba leaf extract group 250 mg/kgBW, the Annona muricata leaf extract group 250 mg/kgBW and a combination of mangrove (Avicennia alba) leaves and soursop (Annona muricata) leaves extract 1:1, all treatments were induced by 1% acetic acid intraperitoneally, the mice’s writhing was observed every 5 minutes for 30 minutes and analyzed using ANOVA and LSD tests. The results showed that the combination of ethanol extracts from mangrove (Avicennia alba) leaves and soursop (Annona muricata) leaves provided the same analgesic effect as the positive control (mefenamic acid).